2013
DOI: 10.3238/arztebl.2013.0591
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Proximal Humeral Fracture in Adults

Abstract: Current evidence supports the individualized treatment of proximal humeral fractures. Treatment decisions must always be made jointly with the patient in consideration of his or her individual needs and characteristics. Particularly for elderly patients, the possibility of conservative treatment should be carefully considered. If conservative treatment is not possible, then the type of operation performed should also be a function of the surgeon's individual skills and experience with particular types of impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 24 publications
2
42
1
13
Order By: Relevance
“…Mean age of the patients was 56 years (range, 35-72 years). Fall while walking (22) was the most common mode of injury followed by fall from height (3) and road traffic accident (2). Average time between injury to surgery was 7 days (range, 1-20 day/s).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean age of the patients was 56 years (range, 35-72 years). Fall while walking (22) was the most common mode of injury followed by fall from height (3) and road traffic accident (2). Average time between injury to surgery was 7 days (range, 1-20 day/s).…”
Section: Resultsmentioning
confidence: 99%
“…Although proximal humeral fracture is a common type of fracture, very few randomized trials of its treatment have been published. The wide variety of fracture morphologies and treatment options, ranging from conservative treatment to various osteosynthesis methods to the implantation of an endoprosthesis, makes such trials difficult to initiate [2] . It is universally recognized that non-displaced fractures can be treated conservatively.…”
Section: Introductionmentioning
confidence: 99%
“…There is a major debate about the question of whether to treat the individual patient nonsurgically or operatively [2,12]. In 1970, Charles Neer introduced a proximal humerus fracture (PHF) classification and found in his own hospital-based patient population that 85 % of fractures were nondisplaced and could be treated conservatively [16].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This fracture occurs with an incidence of 105-342 per 100,000 persons per year. 3 It is the third most common fracture type in patients older than sixty-five, 4 and seventh most common fracture type overall. 5 Systematic reviews have revealed that more data are needed to determine the ideal treatment of proximal humerus fractures.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to treatment, non-operative management, operative reduction and internal fixation (ORIF) and arthroplasty have all been debated in the literature, with arguments for and against each, some particular to older patients. 3,4,11,12 We sought to determine if there is a chronological age after which the benefits of operative treatment for proximal humerus fractures decay. Towards this end we compared a cohort of patients aged seventy or greater to a younger elderly group aged fifty-five to sixty-nine, all treated operatively using a locking plate for proximal humerus fractures.…”
Section: Introductionmentioning
confidence: 99%